Senna occidentalis poisoning in cattle: report of 8 outbreaks in northwestern Argentina - Ovelar, Florencia; Medina, Diego M.; Colque Caro, Luis Adrián; Avellaneda Cáceres, Agustín; Aguirre Castro, Laura Sabrina; Sandoval, Gabriela Virginia; Ruiz, Álvaro Francisco; Micheloud, Juan Francisco (Ediciones INTA, 2024)
Senna occidentalis is one of the many Senna species present in Argentina known for its toxicity to cardiac muscles and large muscle masses. However, there are only a few reports about S. occidentalis poisoning in cattle to date in Argentina. This work aims to describe a retrospective study, which includes 8 outbreaks of S. occidentalis poisoning in cattle from northwestern Argentina. The clinical, pathological, and epidemiological aspects of each outbreak were also detailed. The affected animals showed weakness, incoordination, and myoclonus of large muscle masses. Some animals also showed non-specific clinical signs like depression, anorexia, weight loss, and recumbency before death. The main macroscopic finding was muscle necrosis in large muscle masses and the histological findings included multifocal segmental degeneration and necrosis of muscle fibers. Serum samples collected from the necropsied animals showed a high CPK activity in the most acute cases.